STUDENTS’ PERCEPTION OF USING GRAMMARLY WEBSITE TO SUPPORT THEIR ENGLISH WRITING SKILL - Komara, Cahya; Ramadhan Putra, Andhika (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study seeks to reveal university students' perceptions towards Grammarly website which is becoming more popular to be used by them as a medium for writing English well. As we all know, in this modern era or the 21st century, technology developments especially websites or applications have growth rapidly, and it really eases students in performing English. Grammarly is recognized as one of platform that is intended to assist students’ writing of English correctly and precisely. So, this research is focused to expose the EFL student's perception about Grammarly website whether it is positive or negative. Online closed-ended questionnaire was used in this study, and it involved 100 students only on the small-scale context. The findings demonstrated that students believed that using Grammarly would have a positive impact on their English writing in context three aspects of easiness, motivation and satisfaction, and English competence with dominant respond of strongly agree and disagree.